Therapeutic interventions for the management of social communication disorders among school-aged children (2022)
All over the world, social communication and interaction are fundamental aspects of everyday life. From infancy, humans are social beings, gazing at other people and turning towards voices, grasp a finger and even smiles. For social relationship to become possible there is a need to take into consideration the thoughts and feelings of another person. Essentially, it is the understanding that others' thought is different from one's thought that makes social interaction possible. However, some children experience difficulties with successful social communication and this inability or deficit is termed social communication disorder (SCD). This impaired social language use creates communication difficulties, thereby causing significant impact on academic, adaptive and psychosocial functioning. Additionally, children with SCD has been under identified over time due to its co-occurrence with other conditions which leads to wrong diagnosis, inappropriate therapeutic considerations and non-effective communication as well as poor interpersonal relationship. Thus, this paper, focuses on the causes, incidence, assessment, impact and therapeutic interventions of social communication disorder.